Nanoparticle-based drug delivery systems targeting inflammatory immune mechanisms in acute myocardial infarction: current advances and perspectives - Li, Yuxuan; Li, Peng; Wang, Wujiao; Zhang, Yuanyuan; Li, Sinai; Li, Dong; Lin, Qian (Frontiers in Cardiovascular Medicine, 2025)
Acute myocardial infarction (AMI) remains a major cause of cardiovascular mortality worldwide. The inflammatory immune response after AMI plays a dual role: it facilitates the clearance of necrotic tissue but can also exacerbate injury, significantly affecting patient outcomes. Conventional anti-inflammatory therapies are often limited by systemic toxicity and insufficient targeting, highlighting the need for more refined approaches. This review systematically examines the interplay between AMI's key inflammatory immune mechanisms—including neutrophil N1/N2 phenotypic switching, macrophage M1/M2 polarization, and Treg/Th17 lymphocyte balance—and advancements in nanoparticle-based drug delivery systems (NP-NDDSs) designed to target these mechanisms. NP-NDDSs utilize properties such as size-dependent accumulation, surface functionalization, and stimuli-responsive release (e.g., to pH, ROS, or enzymes) to improve spatiotemporal control over drug delivery. Various nanocarriers, including organic (e.g., liposomes, polymers), inorganic (e.g., gold, silica), and biomimetic (e.g., cell membrane- or exosome-based) systems, have shown potential in influencing neutrophil extracellular trap formation, macrophage phenotype, and lymphocyte activity. These developments suggest that NP-NDDSs could help control excessive inflammation, support tissue repair, and limit adverse remodeling. Nevertheless, challenges in targeting precision, manufacturing scalability, and long-term biosafety remain to be addressed. By summarizing current advances and identifying future needs, this review aims to provide a basis for developing targeted therapies against immune-mediated injury in AMI.